“Why Is Your Interpretation of My Experience the Only One That Counts?” A Comparison of Providers’ and Young Women's Perceptions of Their Needs - Rosenbaum, Jill Leslie (The prison journal, 2024)
This article draws on the author's 2023 Western Society of Criminology Paul Tappan Award address on her seminal work with adolescent girls in Flint Michigan. Echoing the major theme from that address, the article focuses on the need for practitioners and academics to collaborate and more actively engage in targeting programs relevant to the needs of young women. The Flint study identified great discrepancies between providers and girls regarding program relevancy and effectiveness, underscoring the importance of including adolescent girls’ voice in program development and evaluation, which is finally being addressed in contemporary programming.